Cervical Capillary Haemangioma: A Case Report - Sharma, K; Sharma, UK; Sigdel, B (Kathmandu University Medical Journal, 2015)
Capillary haemangioma is a common benign lesion occurring at multiple areas of body. They have unique radiological appearances and are confirmed by histological examinations. However capillary haemangioma of cervical region is a very rare condition. Such a case is presented here. It presented as an extramedullary intradural mass compressing the cord and corresponding root giving rise to myeloradiculopathic symptoms. Total enblock excision of the lesion gave a total cure. Kathmandu University Medical Journal Vol.12(3) 2014; 211-214